Primary production in subsidized green-brown food webs - Zelnik, Yuval R.; Manzoni, Stefano; Bommarco, Riccardo (Frontiers in Ecology and Evolution, 2023)
Ecosystems worldwide receive large amounts of nutrients from both natural processes and human activities. While direct subsidy effects on primary production are relatively well known (the green food web), the indirect effects of subsidies on producers as mediated by the brown food web and predators are poorly considered. With a dynamical green-brown food web model, parameterized using empirical estimates from the literature, we illustrate the effect of organic and inorganic nutrient subsidies on net primary production (i.e., after removing loss to herbivory) in two idealized ecosystems -- one terrestrial and one aquatic. We find that nutrient subsidies increase net primary production, an effect that saturates with increasing subsidies. Changing the quality of subsidies from inorganic to organic tends to increase net primary production in terrestrial ecosystems, but less often so in aquatic ecosystems. This occurs when organic nutrient inputs promote detritivores in the brown food web, and hence predators that in turn regulate herbivores, thereby promoting primary production. This previously largely overlooked effect is further enhanced by ecosystem properties such as fast decomposition and low rates of nutrient additions and demonstrates the importance of nutrient subsidy quality on ecosystem functioning.